2003
DOI: 10.1023/a:1025548623524
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Although it has been known for quite some time that genomic methylation is significantly altered in aging and neoplastic tissues and cells, the underlying mechanisms responsible for these alterations are not yet known. Since DNA methylation affects many different cellular processes including, most significantly, gene expression, elucidation of the basis for aberrations in DNA methylation in aging and cancer is of high priority. To address this problem, we sought to analyze changes in gene expression, protein p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(48 citation statements)
references
References 41 publications
3
45
0
Order By: Relevance
“…The physiological function of this low-level methylation is unclear, especially at genes whose CpG island methylation is thought to contribute to cancer, such as SFRP2 and IRAK3 (refs 41,44); in fact, here methylation may reflect a form of ‘epigenetic damage’ in stressed senescent cells (see below). Increases in DNA methylation might involve DNMTs other than DNMT1, such as the de novo methyltransferase DNMT3B (refs 25,45,46; Fig. 3c).…”
Section: Discussionmentioning
confidence: 99%
“…The physiological function of this low-level methylation is unclear, especially at genes whose CpG island methylation is thought to contribute to cancer, such as SFRP2 and IRAK3 (refs 41,44); in fact, here methylation may reflect a form of ‘epigenetic damage’ in stressed senescent cells (see below). Increases in DNA methylation might involve DNMTs other than DNMT1, such as the de novo methyltransferase DNMT3B (refs 25,45,46; Fig. 3c).…”
Section: Discussionmentioning
confidence: 99%
“…However, the extent of DNA methylation may reflect changes in both intrinsic and environmental exposure [32]. For instance, studies in humans indicated that total genomic 5-methylcytosine has been found to typically decrease during aging [33,34], in concordance with declining Dnmt1 activity with age [35]. Parasites such as T. spiralis certainly undergo more drastic lifespan changes in response to environmental cues, that is, metamorphosis critical to their survival and reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…43 In aging and immortalized fibroblasts, Dnmt1 expression and activity decrease, concomitantly with an upregulation of Dnmt3b transcription. 44,45 DNA methylation serves as a docking site for Methyl-CpG-binding proteins (MBPs) constitutive heterochromatin. Consistent with the loss of pericentric heterochromatin, pericentric satellite III repeat transcription is derepressed.…”
Section: Global Heterochromatin Lossmentioning
confidence: 99%